Charakter prawny instytucji przepadku po zmianach nowelizacyjnych wprowadzonych do Kodeksu karnego ustawą z dnia 20 lutego 2015 r. - Płońska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The legal nature of the institution of forfeiture following the changes to the Criminal Code introduced by the Amendment Act of February 20th, 2015
Keywords: nowelizacja kodeksu karnego; kodeks karny; przepadek; korzyść materialna